2020
DOI: 10.26633/rpsp.2020.17
|View full text |Cite
|
Sign up to set email alerts
|

Características sociodemográficas asociadas a la prevalencia del consumo de tabaco en Costa Rica

Abstract: Objetivo. Determinar las asociaciones existentes entre las características sociodemográficas y la prevalencia del consumo actual de tabaco en Costa Rica, según los resultados de la Encuesta Global de Tabaquismo en Adultos (GATS). Métodos. Estudio epidemiológico, observacional de tipo transversal con representación nacional (n = 8607), que utilizó las variables sociodemográficas incluidas en la GATS realizada durante 2015. Se diseñó un modelo de regresión logística para predecir la influencia de esas variables … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
4
0
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 13 publications
(12 citation statements)
references
References 22 publications
(14 reference statements)
0
4
0
2
Order By: Relevance
“…The protective effect of mixed and rural areas in men might be explained by health risky behaviors. For example, in a recent study regarding the social determinants of tobacco consumption in Costa Rica, we showed the presence of a strong protective effect of rural area in tobacco consumption, after adjustment for socioeconomic factors (32). Since tobacco consumption is far more prevalent in men compared to women, this might explained why mixed and rural areas have a protective effect in men.…”
Section: Discussionmentioning
confidence: 64%
“…The protective effect of mixed and rural areas in men might be explained by health risky behaviors. For example, in a recent study regarding the social determinants of tobacco consumption in Costa Rica, we showed the presence of a strong protective effect of rural area in tobacco consumption, after adjustment for socioeconomic factors (32). Since tobacco consumption is far more prevalent in men compared to women, this might explained why mixed and rural areas have a protective effect in men.…”
Section: Discussionmentioning
confidence: 64%
“…These two factors could thus affect the socioeconomic characteristics of the population less than in other countries. In men, smoking prevalence is lower in rural areas than in urban areas, but it is weakly-linked to socioeconomic status 37 . Studies suggest that alcohol consumption has a positive social gradient, where the privileged drink more than the underprivileged 39 , 40 .…”
Section: Discussionmentioning
confidence: 96%
“…Describing the distribution of risky health behaviors according to urbanicity and socioeconomic indicators is thus essential to contextualize the results of our study. In Costa Rica, smoking prevalence is low, especially for women (4%) 37 , and alcohol consumption is lower than in the United States or Europe 38 . These two factors could thus affect the socioeconomic characteristics of the population less than in other countries.…”
Section: Discussionmentioning
confidence: 98%
“…Por ejemplo, una de las ediciones de la Revista Peruana de Medicina Experimental y Salud Pública (Burstein, 2013), incluyó diversas investigaciones sobre ISS, analizando su relación con eventos como la mortalidad infantil, la tuberculosis, la malnutrición, daño genotóxico, entre otros. Asimismo, otras investigaciones analizaron las inequidades vinculadas con el tabaquismo (Hosseinpoor et al, 2011;Espinoza-Aguirre et al, 2020), la pérdida de piezas dentales (Barboza Solís y Fantin, 2017), los accidentes de tránsito (Nantulya y Muli-Musiime, 2002), el dengue (Alvarado-Prado y Nieto, 2019), el cáncer (Fantin et al, 2020a) o más ampliamente la mortalidad (Gallo et al, 2012), entre otros. Como se señaló antes, esto responde también a las reflexiones metodológicas sobre el "recorte de la realidad" 7 (Batthyány y Cabrera, 2011, pp.10-11).…”
Section: Recomendación 2: Precisión Del Planteamiento Del Problema De...unclassified